Applied single subjects research for school psychologists and educators - Finch, W. Holmes; Hernandez Finch, Maria; Hazelwood, Alicia (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"This book will be written primarily for graduate students, advanced undergraduates, and professionals in the fields of school psychology, special education, and other areas of education, as well as the health professions. We see the book as being a viable textbook for courses in research design, applied statistics, applied behavioral analysis, and practicum, among others. We would not assume of the readers any prior knowledge about single subjects designs, nor any prior statistical experience. We will provide an introductory chapter devoted to basic statistical concepts, including measures of central tendency (e.g., mean, median, mode), measures of variation (e.g., variance, standard deviation, range, inter-quartile range), correlation, frequency distributions, and effect sizes. In addition, given that the book will rely heavily on Microsoft Excel software, the introductory chapter will also devote attention to the basics of using the software for organizing data, conducting basic statistical analyses, and for graphics. The Excel commands used to carry out these analyses will be largely automated so that users will only need to define the range for their data, and then enter it into the Excel spreadsheet. We envision these tools being available on the book website, with instructions for using them available in the book itself. We envision the book as being useful either as a primary text for a course in educational research designs, school psychology practicum, applied behavioral analysis, special education, or applied statistics. We also anticipate that individuals working in schools, school districts, mental health facilities, hospitals, applied behavioral analysis clinics, and evaluation organizations, as well as faculty members needing a practical resource for single subject design research, will all serve as a market for the book. In short, the readership would include graduate students, faculty members, teachers, psychologists, social workers, counselors, medical professionals, applied behavioral analysis professionals, program evaluators, and others whose work focuses on monitoring changes in individuals, particularly as the result of specific treatment conditions. We believe that this book could be marketed through professional organizations such as the American Educational Research Association (AERA), the National Association of School Psychologists, the National Association of Special Education Teachers, the Association for Professional Behavior Analysis, the American Psychological Association (APA), the Association for Psychological Science, and the American Evaluation Association. Within AERA, the following special interest groups would have particular interest in this book: Action Research, Classroom Observation, Disability Studies in Education, Mixed Methods Research, Qualitative Research, and Special Education Research. The book could also be marketed to state departments of education and their special education and school psychology divisions. Currently, many state departments of education require documentation for Response to Intervention (RtI) and Multi-Tiered Systems of Support (MTSS) procedures for individual students. The method taught in this proposed book would allow educators and student support personnel to document the effectiveness of interventions systematically and accurately"-- Provided by publisher.
Keywords: Educational psychology -- Data processing -- Textbooks.; Single subject research -- Textbooks.; Educational statistics -- Textbooks.; Education -- Educational Psychology.; Educational psychology.; elektronické knihy; electronic books